Flea Infestations on Domestic Animals in Nafusa Mountain Region, North-West Libya - Aboulqassim , Waleed Y. M.; Ghana, Salah; Shaibi, Taher (Al-Mukhtar Journal of Sciences, 2022)
Fleas are ectoparasitic pests on domestic animals and act as vectors of many pathogens to humans. Here, we aim to identify the fleas that parasitize on domestic animals and their seasonality in the Nafusa Mountain region (Gharyan, Zintan, and Nalut). The survey was carried out from summer 2017 to winter 2018/2019. Fleas were collected seasonally from flea-infested animals using a metal comb (11 teeth per cm) and tweezers. One flea species was identified in this survey; Ctenocephalides felis, which was collected from goats, sheep, rabbits, donkeys, hens, cats, and dogs. The highest flea prevalence was among goats (66.49 %), followed by sheep (56.17%), whereas in dogs, donkeys, hens, rabbits, and cats, it represented less than 50.00%. The highest flea intensity was among dogs (4.50 ± 3.04 fleas per dog), while the lowest intensity was among hens (0.87 ± 0.59 fleas per hen). The highest mean flea abundance was among cats (8.00), whereas goats, sheep, donkeys, dogs, and hens represented less than 1.50 fleas per host. Summer and autumn represented the highest intensity followed by spring, but no fleas were collected in winter. The finding of the study indicated that Ct. felis was common among domestic animals. Consequently, it may become a potential source of pathogen transmission among people and animals.